Nutritional Composition of Biscuits from Wheat-Sweet Potato-Soybean Composite Flour - Ponka Roger; Bisso Monesso Marvist Bertrand; Zomegni Gaston; Bissada Nouhman; Fokou Elie (International Journal of Food Science)
The aim of this study was to evaluate the nutritional composition of biscuits from wheat-sweet potato-soybean composite flours. Substitutions of wheat flour with sweet potato and soybean flours at the rate of 25% (wheat flour 375 g, sweet potato flour 100 g, and soybean flour 25 g) (T1), 50% (wheat flour 250 g, sweet potato flour 200 g, and soybean flour 50 g) (T2), 75% (wheat flour 125 g, sweet potato flour 300 g, and soybean flour 75 g) (T3), and 100% (wheat flour 0 g, sweet potato flour 400 g, and soybean flour 100 g) (T4) were made to obtain the wheat-sweet potato-soybean composite flours. Wheat flour without sweet potato and soybean flour was used as control (T0). The functional properties (water absorption capacity and water solubility index) of the flours were determined. Sensory evaluation of biscuits was determined. The proximate and mineral contents of the most preferred biscuits were determined. Results showed that the substitution significantly increases the functional properties of the flours (P<0.05). Sample 75% (T3) is the most preferred biscuit. The incorporation of sweet potato and soy flour in the formulation significantly increases the moisture, fat, protein, fiber, copper, manganese, calcium, magnesium, and potassium contents of the biscuits (P<0.05). Biscuit 75% (T3) records the highest levels in protein and fiber while sample T0 (control) records the highest levels of iron, zinc, and sodium. In terms of overall acceptability and nutrient contents, sample 75% (T3) is the best biscuits.